2021
DOI: 10.3390/nu13124380
|View full text |Cite
|
Sign up to set email alerts
|

A High Protein Diet Is More Effective in Improving Insulin Resistance and Glycemic Variability Compared to a Mediterranean Diet—A Cross-Over Controlled Inpatient Dietary Study

Abstract: The optimal dietary pattern to improve metabolic function remains elusive. In a 21-day randomized controlled inpatient crossover feeding trial of 20 insulin-resistant obese women, we assessed the extent to which two isocaloric dietary interventions—Mediterranean (M) and high protein (HP)—improved metabolic parameters. Obese women were assigned to one of the following dietary sequences: M–HP or HP–M. Cardiometabolic parameters, body weight, glucose monitoring and gut microbiome composition were assessed. Sixtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 46 publications
2
30
0
Order By: Relevance
“…Approximately 65% of the participating subjects were women. The Italian studies were 50% of the total ( 24 33 ), while the other weight reduction programs were conducted in the USA ( 34 36 ), Norway ( 37 , 38 ), Germany ( 39 , 40 ), Czechia ( 41 ), Brasil ( 42 ), and Taiwan ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Approximately 65% of the participating subjects were women. The Italian studies were 50% of the total ( 24 33 ), while the other weight reduction programs were conducted in the USA ( 34 36 ), Norway ( 37 , 38 ), Germany ( 39 , 40 ), Czechia ( 41 ), Brasil ( 42 ), and Taiwan ( 43 ).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion and exclusion criteria heavily depended on the context, in particular, studies that took into consideration routine treatments had less specific criteria. Age was chosen as a cut-off for inclusion only in three studies ( 27 , 33 , 35 ) and three studies recruited only women ( 33 , 34 , 41 ). The study design was largely dependent on its aim.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coprococcus, for example, might exert a positive effect through the production of SCFAs. Moreover, Lachnoclostridium species might metabolize precursors of trimethylamine and its oxide, which negatively regulate glucose metabolism and insulin sensitivity (68). Another study assessed baseline characteristics to predict the postprandial glucose response and revealed that the relative abundance of Faecalibacterium is negatively associated with plasma glucose after the consumption of high-and low-resistant starch (69).…”
Section: Alternative Diet-based Strategies Showing the Predictive Val...mentioning
confidence: 99%